Utilization of Plastic Bottle Waste as Material for Making Sustainable Cement-Less Aesthetic Paving Blocks - Karisma, Dwifi Aprillia; Nursandah, Fauzie; Rahmawaty, Fitry (Universitas Negeri Yogyakarta, 2023)
Plastic is a key ingredient in many products around the world, but its existence has caused serious problems due to the buildup of waste it produces. The construction industry is one of the sectors that can play a role in the utilization of plastic waste. One of them is in the production of paving blocks. This study aims to combine aesthetic aspects and environmental attractiveness in paving blocks without sustainable cement. An experimental method was chosen to develop an alternative to making sustainable paving blocks without the use of cement. Variations used to start from 20% PET: 80% aggregate, 25% PET: 75% aggregate, 30% PET: 70% aggregate, 35% PET: 65% aggregate, 40% PET: 60% aggregate. The aggregates used are sand and stone ash. Physical and mechanical qualities of paving blocks, such as compressive strength, absorption is carried out to determine the quality of paving blocks. The aesthetic aspect is also in focus by carrying out the concept of